2013
DOI: 10.1038/jhh.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Intake of total protein, plant protein and animal protein in relation to blood pressure: a meta-analysis of observational and intervention studies

Abstract: There is growing evidence from epidemiological studies that dietary protein may beneficially influence blood pressure (BP), but findings are inconclusive. We performed a meta-analysis of 29 observational studies and randomized controlled trials (RCTs) of dietary protein and types of protein in relation to BP or incident hypertension, published until January 2012. The analysis included eight cross-sectional studies (n=48 985), four prospective studies (n=11 761) and 17 RCTs (n=1449). A modest inverse associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 36 publications
4
40
1
Order By: Relevance
“…Although the relationship between the dietary protein intake and blood pressure remains controversial (16,17), recent evidence from randomized controlled trials suggests that an increased intake of protein may lower blood pressure (18)(19)(20)(21)(22)(23)(24)(25). The slightly decreased levels of serum albumin observed in apparently healthy subjects in the present study may possibly result from an inadequate protein intake.…”
Section: Discussionmentioning
confidence: 51%
“…Although the relationship between the dietary protein intake and blood pressure remains controversial (16,17), recent evidence from randomized controlled trials suggests that an increased intake of protein may lower blood pressure (18)(19)(20)(21)(22)(23)(24)(25). The slightly decreased levels of serum albumin observed in apparently healthy subjects in the present study may possibly result from an inadequate protein intake.…”
Section: Discussionmentioning
confidence: 51%
“…We used the distributed food/nutrient intake data of each individous studies have suggested that there is an inverse association between total protein intake and blood pressure [2][3][4] . On the other hand, a recent meta-analysis of RCT and intervention studies reported an inverse association between vegetable protein and blood pressure levels 5,6) . However, it remains unclear whether the intake of animal protein or vegetable protein is inversely associated with blood pressure levels [7][8][9][10][11][12][13][14][15] .…”
Section: Dietary Surveymentioning
confidence: 99%
“…Accepted for publication: May 11, 2018 Published online: August 9, 2018 6 observed an inverse association between vegetable protein intake and blood pressure levels in randomly selected men and women aged 40 -59 years old living in Japan, China, United States, and United Kingdom during 1996 to 1997. By contrast, a cross-sectional study of community dwellers in Japan conducted by Umesawa et al 15) showed that blood pressure level has an inverse association with total protein and animal protein intake but no association with vegetable protein intake.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…39 A recent meta-analysis of trials that were stratified by plant protein or animal protein indicated no differences with protein from plant or animal sources. 40 However, the sample size of this meta-analysis was small (three trials, N=327 for plant protein; four trials, N=574 for animal protein), and the effects of plant or animal protein were not directly compared. Hence, further intervention studies and meta-analyses are needed to understand the effects of different sources of protein on BP.…”
Section: Protein Sourcementioning
confidence: 99%